(untitled) (International Journal of Innovative Research in Engineering & Management, 2024)
In today’s globalized world, the interconnection between the economy and the environment is evident. A nation’s prosperity and self-reliance hinge on adopting sustainable methods of energy production. Lack of energy security and self-sufficiency compels a country to import necessary energy resources, significantly impacting both sustainability and the foreign reserves. This paper addresses India’s suboptimal utilization of energy resources, focusing on the import dependency in the energy sector due to the prevalent use of fossil fuel-based energy (conventional energy) from 2006 to 2020. Data analysis, incorporating graphical representations of conventional energy import and consumption, highlights the status, growth, and import dependency trends. The findings reveal that India heavily relies on imports for conventional energy resources, particularly crude oil. The paper concludes that the key solution for improving economic and environmental conditions lies in transitioning towards renewable energy resources.